Predlog Socialistične stranke Slovenije oktobra 1990 za izvedbo plebiscita o samostojnosti Republike Slovenije in odzivi nanj v Sloveniji - Osojnik, Janez (Studia Historica Slovenica, 2022)
Based on an analysis of archival material, which is kept by the Archive of the Republic of Slovenia, published sources, the Slovenian press and the most relevant scientific literature, the article focuses on the plebiscite initiative of The Socialist Party of Slovenia. The initiative was submitted to the Slovenian Assembly on October 2 and presented by the delegates of the party at a meeting of the Assembly two days later. The article describes the origins of the plebiscite initiative, its impact on Slovenian politics and reactions of the latter to the initiative. In addition, we discuss the inclination of Slovenian politics towards the use of the referendum or plebiscite in the early autumn of 1990 in general to achieve the goal of the independence of the Republic of Slovenia, and how the political participation of the people was viewed by the Slovenian public.
Keywords: 1990; disintegration of Yugoslavia; independence; osamosvojitev; plebiscit; plebiscite; razpad Jugoslavije; referendum; Republic of Slovenia; samoodločba; self-determination; Slovenija; Socialis Party of Slovenia; Socialistična stranka Slovenije